COVID-19 Pandemic and Law No. 6 Year 2018 regarding Health Quarantine - Widjaja, Gunawan (UI Scholars Hub, 2020)
By late March, to anticipate the spreading of COVID-19 pandemic, the President of the Republic of Indonesia has issued several regulations. The Author has examined that the main laws that were used as the based for the issuance of those regulations are Law No.6 Year 2018 regarding Health Quarantine (the Health Quarantine Law). Therefore in order to handle COVID-19 pandemic, an understanding of the Law become a must. The aim of this research is to elaborate and explain the Health Quarantine Law to reduce the COVID-19 pandemic. This research is normative legal research. The research used secondary data, which consisted of primary legal sources and secondary legal sources. Data were collected through the